Synergistic effect of the combination of Cinnamomum burmanii, vigna unguiculata, and papain exracts derived from carica papaya latex against C. albicans biofilms degradation - Muhammad Luthfi; Indah Listiana Kriswandini; Fitriah Hasan Zaba (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Candidiasis is an opportunistic infection commonly occurs on host with immunodeficiency, organ transplantation, leukopenia, or radiation therapy. Biofilms are structures that protect C. albicans from antifungals treatments. C. albicans biofilms display multidrug resistance to antifungal agents. Purpose: This study aimed to know whether the combination of Cinnamomum burmannii, Vigna unguiculata, and Papain extracts derived from Carica papaya latex has inadequate inhibitory effects against C.albicans biofilms compared to the combination of Cinnamomum burmannii and Vigna unguiculata extracts. Method: C. albicans. growing on SDA were dissolved in 1 McFarland of sterile aquadest. Micro-plate was filled with 180 µL of SDB, glucose 8%, and 20 µL of C. albicans. Suspension was incubated at 37oC overnight. Extracts were added and incubated for 24 hours. Then, each well was washed with distilled water, and stained with crystal violet 0.1% for 15 minutes. Afterward, each well was washed with distilled water and immediately stained with acetic acid. After 15 minutes of staining, the suspension was transferred to a new well, then measured with micro-plate reader at 595 nm. Results: The combination of Cinnamomum burmanii and Vigna unguiculata extracts had adequate inhibitory effects which is equal to 60.75%. Inhibition increased to 72.09%, 79.06%, and 79.50% after Papain derived from Carica papaya latex was added on concentrations of 138 mg/mL, 276 mg/mL, and 552 mg/mL. Conclusion: The combination of Cinnamomum burmanii (0.25µg/mL), Vigna unguiculata (200 µg/mL), and Papain (276 µg/mL) extracts showed an optimum synergic inhibition for C. albicans biofilms.